The Influence of Product Imitation, Price, and Social Media Marketing on Consumer Confusion among Jims Honey Bag Consumers - Septi Apriliyanti; Ramlah Puji Astuti (IJEBD (International Journal of Entrepreneurship and Business Development), 2026)
This study aims to analyze the influence of product imitation, price, and social media marketing on consumer confusion among consumers of Jims Honey bags in Cirebon City. The phenomenon of consumer confusion is increasingly common in Indonesia due to the high level of imitation of local fashion products in both online and offline markets. Marketplace data indicates that there are more than 3,860 product listings resembling Jims Honey, with the growth of imitation products reaching 35% year-over-year in 2024. Using an associative quantitative approach with a survey design, data were collected from 110 consumers through an online questionnaire and analyzed using PLS-SEM with SmartPLS 4.0. The results show that all three variables significantly influence consumer confusion. Price shows the highest influence with a path coefficient of 0.554 (t = 5.659; p = 0.000), followed by product imitation with a coefficient of 0.295 (t = 5.089; p = 0.000), and social media marketing with a coefficient of 0.152 (t = 2.661; p = 0.008). This study enriches Consumer Confusion Theory in the context of Indonesian local fashion products, demonstrating that consumer confusion is a systemic phenomenon arising from the complexity of market arrangements. The practical implications suggest that local brands need to focus their strategies on clear product differentiation, consistency in transparent pricing systems, and informative digital communication. Future research is recommended to expand the geographical context and product categories and to employ a longitudinal approach to better understand the dynamics of consumer confusion more comprehensively.